The impact of adding PH adjuster additives on the performance of the radiator in 160 cc Vario motorcycles - Naufal Rezza Qur’anal; Ali Akbar; Mulyadi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The vehicle's power comes from the engine, which uses combustion to transform the chemical energy of the fuel into mechanical energy. The combustion temperature will have an impact on the engine's operating temperature if this situation is not adequately cooled. According to some literature, the PH adjuster additive is a combination of chemicals that works to raise the PH and alkalinity of water to improve the state of the water atoms for the cooling process. However, the process of cooling a vehicle radiator with water from the engine is very hot, so further study is required. Additionally, this PH adjuster may condition the water to your specifications. The purpose of this study is to ascertain the outcome of adding the PH adjuster additive composition to the radiator water of the 160 cc Vario motorcycle. The approach is a descriptive methodology based on the outcomes of experiments. According to research based on the experiments carried out in this study, adding 3% PH Adjuster additives at 1000 rpm will produce the best engine performance. The amount of additives added also had an impact on the radiator performance of the 160 cc Vario motorcycle